A METHODOLOGY FOR DEVELOPING SPEAKING SKILLS OF SPECIALIZED SCHOOL STUDENTS THROUGH ARTIFICIAL INTELLIGENCE TECHNOLOGIES (Journal of Universal Science Research, 2025)
The global advancement of artificial intelligence (AI) has transformed educational systems, particularly language learning environments that demand innovative approaches to teaching speaking skills. Specialized schools, which focus on academic excellence and discipline-specific training, require pedagogical models that leverage technology to enhance communicative competence. This article presents a comprehensive academic examination of AI-based methodologies for improving speaking skills in specialized school students. It draws on communicative, sociocultural, and cognitive theories of language learning; synthesizes recent empirical research; identifies existing challenges in traditional speaking instruction; and proposes an integrated methodology for AI-supported speaking development. The methodology includes stages of needs analysis, instructional planning, AI-mediated practice, automated assessment, and reflective learning. The study contributes to both theoretical understanding and practical approaches to AI-driven pedagogy, offering implications for curriculum design, teacher professional development, and the future of language education in specialized school contexts.